Mapping the open-source ecosystem - Davies, Ryan (School of Economics, 2025)
Unlike private data, which is not traceable, open-source software is traceable and the dependencies between different libraries and modules of open-source software can best be described as a network Similarly to academic papers in a field of research, projects in an open-source ecosystem use the work of others and are subsequently used by others as research advances. This dissertation uses tools from citation networks and applies them to dependencies in open-source networks taken from the dataset provided by Libraries.io in order to understand the structure and prevailing patterns inherent to open source ecosystems.